Predictors of carotid artery restenosis after carotid endarterectomy - E. P. Kolesova; E. V. Verkhovskaya; A. G. Vanyurkin; E. K. Zaykova; V. V. Kvan; O. V. Kalinina; M. A. Chernyavsky; A. L. Maslyansky; A. N. Yakovlev; A. Yu. Babenko; A. O. Konradi; E. V. Shlyakhto (Российский кардиологический журнал)
Aim. To determine predictors of carotid artery restenosis in patients after carotid endarterectomy (CEA).Material and methods. The study included 100 patients with stenosing carotid atherosclerosis who underwent CEA. We performed biochemical and clinical screening tests, computed tomography angiography and carotid duplex ultrasound before and after surgery. The median follow-up was 1,9 years [1,4;2,25]. During the prospective follow-up, we selected patients with postoperative restenosis and a control group of patients without restenosis with most complete data on postoperative period, including carotid duplex ultrasound and end points. The final analysis included 76 patients as follows: 55 men (mean age, 67 years) and 21 women (mean age, 66,5 years). Depending on the degree of restenosis, patients were divided into following groups: no restenosis (0-19%), moderate restenosis (20-50%), significant restenosis (from 51%).Results. According to multivariate regression analysis, the key predictors of restenosis were glucose level, atherogenicity coefficient and glomerular filtration rate (GFR). Significant parameters associated with the severity of restenosis were GFR, glucose level, linear blood flow velocity after surgery, body mass index and age (all laboratory parameters were assessed before surgery). In patients without restenosis, differences were observed compared to the group with moderate restenosis in such factors as atherogenicity coefficient, fibrinogen, glucose and prothrombin levels, as well as smoking. In addition, the group with severe restenosis showed significant differences from the group without restenosis in GFR. The incidence of restenosis increases 12 months after surgery, reaching its peak by two years of follow-up. We did not reveal significant associations of the type of surgery (classical/eversion CEA) with various postoperative complications, with the exception of thrombosis in the early postoperative period.Conclusion. Thus, according to our study, the likelihood of restenosis was associated with traditional risk factors for cardiovascular diseases, such as impaired carbohydrate and lipid metabolism, inflammation, decreased GFR and obesity, and raises with an increase in the postoperative follow-up period. The data obtained suggest that the mechanisms underlying the pathogenesis of restenosis are similar to those leading to atherosclerosis.